Insulin-Like Growth Factor-I Induces Arginase Activity in Leishmania amazonensis Amastigote-Infected Macrophages through a Cytokine-Independent Mechanism. (9th September 2014) - Vendrame, Celia Maria Vieira; Carvalho, Marcia Dias Teixeira; Tempone, Andre Gustavo; Goto, Hiro
Abstract : Leishmania (Leishmania) amazonensis exhibits peculiarities in its interactions with hosts. Because amastigotes are the primary form associated with the progression of infection, we studied the effect of insulin-like growth factor (IGF)-I on interactions between L. (L.) amazonensis amastigotes and macrophages. Upon stimulation of infected macrophages with IGF-I, we observed decreased nitric oxide production but increased arginase expression and activity, which lead to increased parasitism. However, stimulation of amastigote-infected macrophages with IGF-I did not result in altered cytokine levels compared to unstimulated controls. Because IGF-I is present in tissue fluids and also within macrophages, we examined the possible effect of this factor on phosphatidylserine (PS) exposure on amastigotes, seen previously in tissue-derived amastigotes leading to increased parasitism. Stimulation with IGF-I induced PS exposure on amastigotes but not on promastigotes. Using a PS-liposome instead of amastigotes, we observed that the PS-liposome but not the control phosphatidylcholine-liposome led to increased arginase activity in macrophages, and this process was not blocked by anti-TGF- β antibodies. Our results suggest that in L. (L.) amazonensis amastigote-infected macrophages, IGF-I induces arginase activity directly in amastigotes and in macrophages through the induction of PS exposure on amastigotes in the latter, which could lead to the alternative activation of macrophages through cytokine-independent mechanisms.